ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI (Studi Pada Penerapan Sistem Informasi Manajemen Daerah (SIMDA) di BPKPD Kota Banjar) - Irman Firmansyah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This research is motivated by the still not optimal performance of the Banjar City Regional Finance and Revenue Management Agency employees which is characterized by frequent recording and reporting errors involving administrative management, the completion of existing work that is not in accordance with work achievement targets, employees who arrive late from work hours entering work that has been determined, besides that employees often leave the effective time of working hours and delays in completing work. The formulation of the problems posed in this study are as follows: 1. How does competence affect employee performance? 2. How does work motivation affect employee performance? 3. How does work discipline affect employee performance? 4. How does competence, motivation and work discipline simultaneously influence employee performance at the BPKPD in Banjar City? The method used in this study uses quantitative methods. Data collection techniques through questionnaires, literature, and documentation. With a research sample of 50 employee respondents and data analysis used through statistical tests of correlation and multiple regression using SPSS version 26.00 for windows. The research results show: 1). Competence tends to be good and employee performance is high, so competence has a positive and significant effect on employee performance. This means that the better the competence, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency. 2). Work motivation tends to be good and employee performance is high, so work motivation has a positive and significant effect on employee performance. This means that the better the work motivation, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency. 3). Work discipline tends to be good and employee performance is high, so work discipline has a positive and significant effect on employee performance. This means that the better the work discipline, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency 4). Competence, motivation and work discipline tend to be good and employee performance is high, so that competence, motivation and work discipline have a positive and significant effect on employee performance. This means that the better the competence, motivation and work discipline, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency.